A kind of organic silicon potting glue and preparation method thereof
By using a combined filler of modified alumina particles, ceria nanoparticles and core-shell structural composites in silicone potting, combining end vinyl silicone oil and hydrogen-containing silicone oil, silicone oil in the prior art, silicone potting in the prior art is solved The problems of low thermal conductivity, poor flame retardant performance and poor viscosity have achieved a significant improvement in thermal conductivity, flame retardancy and viscosity, and are suitable for the electronics industry.
Patent Information
- Application Number
- CN202410429555.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-10
AI Technical Summary
The existing addition-formed silicone potting adhesives have low thermal conductivity, poor flame retardant properties and poor viscosity, which limits their application in the electronics industry.
The combination of modified alumina particles, ceria nanoparticles and core-shell structural composites with polyhexanate butadiene terephthalate as the core and chitosan and Si as the shell are used as fillers, and the terminal ethylene is bound to the end Base silicone oil and hydrogen-containing silicone oil are added with inhibitors and Caster catalysts, and through the combined action of vacuum conditions and alternating current field, silicone potting adhesives with good thermal conductivity, flame retardant and good viscosity are prepared.
It has achieved a significant improvement in the thermal conductivity, flame retardancy and viscosity of silicone potting adhesives. It is suitable for the electronics industry, and the preparation method is simple, efficient and cost-saving.
Smart Images

Figure BDA0004785159280000061 
Figure BDA0004785159280000071 
Figure BDA0004785159280000121
Abstract
Description
Technical Field
[0001] The present application relates to the field of organic silicon potting adhesive, and more specifically, to an organic silicon potting adhesive and a preparation method thereof. Background Art
[0002] Potting compound is a liquid compound that is mechanically or manually loaded into the device and solidified at room temperature or under heating conditions to become a polymer material with excellent performance. The types of potting compounds include silicone potting compound, epoxy potting compound, polyurethane potting compound, etc.
[0003] In the field of electronics industry, in order to improve the stability and reliability of electronic components and integrated circuits, it is often necessary to potting electronic assembly parts so that they can adapt to harsh environments such as moisture, salt spray, dust, vibration, impact, high and low temperature, etc., so as to ensure that electronic components can work normally. Addition silicone potting glue has excellent electrical insulation properties and good chemical stability, high and low temperature resistance, aging resistance, low moisture absorption and simple processing technology, and is a material with great development prospects for the electronics industry.
[0004] However, common addition-type silicone potting glue has the following shortcomings in application: first, the thermal conductivity is low, only about 0.2W·m-1·K-1; second, the flame retardant performance is poor, and it can burn completely once ignited; third, after the addition-type silicone potting glue is cured, most of the surface is non-polar organic groups, so the viscosity is very poor. These problems seriously limit the application scope of addition-type silicone potting glue. Therefore, there is an urgent need for a silicone potting glue with good thermal conductivity, flame retardancy and good viscosity. Summary of the invention
[0005] In order to provide an organic silicone potting adhesive with good thermal conductivity, flame retardancy and good viscosity, the present application provides an organic silicone potting adhesive and a preparation method thereof.
[0006] The present application provides a silicone potting adhesive and a preparation method thereof using the following technical solutions:
[0007] In the first aspect, the present application provides a silicone potting adhesive, which adopts the following technical solution:
[0008] A silicone potting adhesive comprises the following components by weight: 90-120 parts of vinyl-terminated silicone oil, 8-15 parts of hydrogen-containing silicone oil, 360-580 parts of filler, 0.1-0.6 parts of inhibitor, and 0.05-0.20 parts of Custer catalyst; the filler is a combination of modified alumina particles and cerium dioxide nanoparticles, and the filler also includes a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell; the ratio of the modified alumina particles, the cerium dioxide nanoparticles, and the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 1:(0.2-0.9):(1-8); the preparation method of the modified alumina particles is as follows:
[0009] S1. Mix 68-84 parts of aluminum oxide micron particles, 42-56 parts of a precipitant, and 1100-1350 parts of distilled water to obtain a reaction mixture;
[0010] S2. The reaction mixture is stirred and dispersed at a speed of 2200-3000 r / min, alum is added while stirring, and after stirring for 7-9 minutes, stirring is stopped, and a precipitation reaction is carried out, and the temperature is maintained at 30-35° C. for 1-1.5 hours, and then filtered to collect the aluminum oxide precipitate with aluminum hydroxide deposited on the surface;
[0011] S3. The collected alumina precipitate was dried in an oven at 100-120°C for 2-4h, then treated in a high temperature sintering furnace at 680-800°C for 2.5-3.5h, and then treated in a high temperature sintering furnace at 1300-1450°C for 1-2.5h, taken out, and dried at room temperature for 24-48h to obtain nano-alumina-coated alumina micron particles;
[0012] S4. Add a silane coupling agent to the nano-alumina-coated alumina micron particles, mix them evenly at a temperature of 35-55° C., and obtain modified alumina particles.
[0013] By adopting the above technical scheme, the prepared silicone potting adhesive has good thermal conductivity, flame retardancy and good viscosity, and is suitable for the field of electronic industry. The vinyl-terminated silicone oil, hydrogen-containing silicone oil, filler, inhibitor and Custer catalyst jointly generate a moderate cross-linking density and good mechanical properties. The filler is a combination of modified alumina particles and cerium dioxide nanoparticles, and the filler also includes a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell, and a combination of modified alumina particles and cerium dioxide nanoparticles, and the filler also includes a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell, and the modified alumina particles, cerium dioxide nanoparticles and the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell are of different types and different morphologies, and are more easily evenly dispersed in the organic silicon potting glue, contact each other, and are more easily densely stacked to form multiple heat conduction paths, so that the organic silicon potting glue with better thermal conductivity can be obtained at a lower filling amount. At the same time, the interaction between the three fillers reduces the possibility of agglomeration of one of the fillers in the silicone rubber matrix, and further improves the thermal conductivity of the organic silicon potting glue. Alumina in the related art will react with water after absorbing moisture to hydrolyze AlN+3H20=Al(OH)3+NH3. The Al(0H)3 produced by hydrolysis will interrupt the heat conduction path, thereby affecting the transmission of phonons. Therefore, the thermal conductivity of the finished product is low. Only using ordinary coupling agents for surface treatment cannot guarantee a good coating effect. In the present application, the modified alumina particles prepared by the above-mentioned preparation method of modified alumina particles have a core of micron-sized alumina particles, and the outer core is uniformly covered with a silane-modified nano-sized alumina shell, which improves the hydrophobic effect of the modified alumina, and can synergize with cerium dioxide nanoparticles and polybutylene adipate terephthalate to improve the mechanical properties, thermal conductivity and viscosity of the silicone potting compound. Cerium dioxide nanoparticles can prevent the oxidation cross-linking of polysiloxane side chains and the cyclization degradation of the main chain. They can prevent the free radical reaction caused by oxidation in silicone rubber within a certain temperature range, and can be regenerated under the action of oxygen in the air. They can absorb certain trace acids or alkaline substances in silicone rubber that can catalyze the degradation reaction, thereby playing a thermal stabilizing role on silicone rubber. In addition, cerium dioxide nanoparticles have a special electronic structure (the f electron layer is not full) that makes it easy to form a complex. The complex formed inhibits the swelling of the silicone potting compound by preventing the segment movement of the molecules in the silicone potting compound, thereby improving the mechanical properties and oil resistance of the silicone potting compound. The core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell has good hydrophobicity and moderate polarity, which is conducive to improving the viscosity of the silicone potting compound.The Si shell in the shell structure can synergize with chitosan and polybutylene adipate terephthalate to improve the flame retardancy of the silicone potting adhesive. In the silicone potting adhesive, it has a high flame retardant efficiency and smoke suppression effect. In summary, the modified alumina particles, cerium dioxide nanoparticles, and the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell synergize. Under the joint action of terminal vinyl silicone oil, hydrogen-containing silicone oil, inhibitor, and Custer catalyst, the prepared silicone potting adhesive has good thermal conductivity, flame retardancy, good viscosity, and good mechanical properties, and is suitable for the field of electronics industry.
[0014] Optionally, the precipitant is aluminum sulfate.
[0015] By adopting the above technical solution, aluminum sulfate is selected as the precipitant, and the coordination effect with alum is better, so that the precipitation reaction of S2 in the preparation method of modified alumina particles is better.
[0016] Optionally, the inner core particle size of the modified alumina particles is 16-20 microns, and the outer shell thickness of the modified alumina particles is 120-160 nm.
[0017] By adopting the above technical scheme, the inner core particle size of the modified alumina particles is 16-20 microns, and the outer shell thickness of the modified alumina particles is 120-160nm, so that in step S4, the modification of the outer shell by the silane coupling agent is more uniform, and the modified alumina particles and other fillers such as cerium dioxide nanoparticles, a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell can produce a dense stacking effect, making the silicone potting glue denser and improving the thermal conductivity and mechanical properties of the silicone potting glue.
[0018] Optionally, the particle size of the cerium dioxide nanoparticles is 50 nanometers.
[0019] By adopting the above technical scheme, the particle size of cerium dioxide nanoparticles is 50 nanometers, which is more conducive to the dense stacking effect of cerium dioxide nanoparticles with modified alumina particles, core-shell structure composites with polybutylene adipate terephthalate as the core and chitosan and Si as the shell, etc., making the silicone potting compound denser and improving the thermal conductivity and mechanical properties of the silicone potting compound.
[0020] Optionally, the preparation method of the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is as follows:
[0021] Prepare chitosan acetic acid aqueous solution: dissolve 0.5-1.5 parts of chitosan in 0.5-1.5wt% acetic acid solution;
[0022] The first core-shell reaction: 8-12 parts of polybutylene adipate terephthalate are uniformly dispersed in 180-230 parts of deionized water, and the prepared chitosan acetic acid aqueous solution is added dropwise, and after stirring for 3-5 minutes, centrifugation is performed for 3-5 minutes at a centrifugal speed of 3000-4000r / min to obtain a precipitate, and then washed with deionized water to obtain a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan as the shell;
[0023] Prepare Si(C00H)2 ammonia solution: dissolve 0.2-0.4 parts of Si(C00H)2 in 9.5-10.5wt% dilute ammonia water, adjust the pH to 8, and prepare Si(C00H)2 ammonia solution;
[0024] The second core-shell reaction: a core-shell structure complex with polybutylene adipate terephthalate as the core and chitosan as the shell is uniformly dispersed in 200-300 parts of deionized water to prepare a suspension, and Si(C00H)2 ammonia solution is added to the suspension, stirred for 3-5 minutes, and centrifuged to obtain a precipitate, which is washed twice with deionized water, ball-milled for 30-60 minutes, and vacuum-dried at 65-85°C for 12-18 hours. The precipitate is sieved to obtain a core-shell structure complex with polybutylene adipate terephthalate as the core and chitosan and Si as the shell.
[0025] By adopting the above technical scheme, the chitosan acetic acid aqueous solution step and the first core-shell reaction step are configured, and the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan as the shell is first obtained through the interaction between polybutylene adipate terephthalate and chitosan. The Si(COOH)2 ammonia solution step and the second core-shell reaction step are configured, and the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is obtained through the interaction between Si and chitosan. In addition, the structural design is also helpful for the filler to be well dispersed in the silicone potting compound, and while giving the silicone potting compound excellent flame retardant properties, the thermal conductivity, mechanical properties and viscosity of the silicone potting compound are all improved to varying degrees.
[0026] Optionally, the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 10-15 microns.
[0027] By adopting the above technical scheme, the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 10-15 microns, which is more conducive to the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell to produce a dense stacking effect together with other fillers such as modified alumina particles and cerium dioxide nanoparticles, making the silicone potting compound denser and improving the thermal conductivity and mechanical properties of the silicone potting compound.
[0028] Optionally, the vinyl-terminated silicone oil is a combination of vinyl-terminated silicone oil with a viscosity of 400mPa·s and vinyl-terminated silicone oil with a viscosity of 800mPa·s, and the ratio of the vinyl-terminated silicone oil with a viscosity of 400mPa·s and the vinyl-terminated silicone oil with a viscosity of 800mPa·s is 1:(2-3).
[0029] By adopting the above technical scheme, the combination of terminal vinyl silicone oil with a viscosity of 400mPa·s and terminal vinyl silicone oil with a viscosity of 800mPa·s is conducive to the preparation of silicone potting adhesive with excellent performance. When the ratio of the terminal vinyl silicone oil with a viscosity of 400mPa·s and the terminal vinyl silicone oil with a viscosity of 800mPa·s is 1:(2-3), the crosslinking density of the silicone potting adhesive is improved, which is conducive to improving the thermal conductivity, viscosity and mechanical properties of the silicone potting adhesive.
[0030] Optionally, the inhibitor is alkynyl cyclohexanol.
[0031] By adopting the above technical solution, the end-vinyl silicone oil, hydrogen-containing silicone oil, filler and catalyst will cross-link quickly at room temperature after mixing, while the addition-type silicone potting glue needs a certain operation time during preparation and use, and a certain shelf life during storage, so a certain amount of inhibitor needs to be added to the formula. The inhibitor is alkynyl cyclohexanol. At room temperature, alkynyl cyclohexanol can form a relatively stable coordination bond with the Custer catalyst, inhibiting the activity of the Custer catalyst. When heated to the curing temperature, the active Custer catalyst will be released, allowing the hydrosilylation reaction to proceed smoothly. As an inhibitor, alkynyl cyclohexanol also has the advantages of high efficiency, mild reaction conditions and non-destructiveness.
[0032] Optionally, the Castel catalyst is a chloroplatinic acid-divinyltetramethyldisiloxane complex.
[0033] By adopting the above technical solution, the Custer catalyst uses chloroplatinic acid-divinyltetramethyldisiloxane complex, which has good compatibility with silicone potting compound and good storage stability.
[0034] In a second aspect, the present application provides a method for preparing a silicone potting compound, using the following technical solution:
[0035] A method for preparing the above-mentioned silicone potting adhesive comprises the following steps:
[0036] Under vacuum conditions, the vinyl-terminated silicone oil and filler are stirred evenly at a temperature of 80-110°C to obtain a base material, which is then cooled to a temperature of 40-50°C. An appropriate amount of hydrogenated silicone oil, inhibitor, and Custer catalyst are added and mixed evenly. Finally, the mixture is vacuum degassed for 15-25 minutes and poured into a mold at a strength of 9-10 kV·mm -1 The organic silicone potting adhesive is cured for 1.5-2.5 hours under a 50Hz alternating electric field and a temperature of 130-170°C to obtain the organic silicone potting adhesive.
[0037] By adopting the above technical scheme, under the action of the AC electric field, the orientation degree of the particles in the filler is higher, and more heat-conducting chains, i.e., heat-conducting paths, are formed inside the silicone potting compound. The prepared silicone potting compound has good thermal conductivity, flame retardancy and good viscosity, and is suitable for the field of electronics industry. The cross-linking density generated by the combined action of the vinyl-terminated silicone oil, hydrogen-containing silicone oil, filler, inhibitor, and Custer catalyst is moderate, and the mechanical properties are good. Furthermore, the preparation method is simple, efficient, and saves costs.
[0038] In summary, this application has the following beneficial effects:
[0039] 1. Since the present application adopts vinyl-terminated silicone oil, hydrogen-containing silicone oil, fillers, inhibitors, and Custer catalysts, the fillers are selected from a combination of a core-shell structure composite of modified alumina particles, cerium dioxide nanoparticles, and polybutylene adipate terephthalate as the core, and chitosan and Si as the shell. The three fillers work synergistically. Under the joint action of vinyl-terminated silicone oil, hydrogen-containing silicone oil, inhibitors, and Custer catalysts, the prepared silicone potting adhesive has good thermal conductivity, flame retardancy, good viscosity, and good mechanical properties, and is suitable for the field of electronics industry.
[0040] 2. In the present application, the core particle size of the modified alumina particles is 16-20 microns, the particle size of the cerium dioxide nanoparticles is 50 nanometers, and the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 10-15 microns. The three fillers are of different sizes, which can produce a dense stacking effect of the fillers, making the silicone potting glue denser and improving the thermal conductivity and mechanical properties of the silicone potting glue.
[0041] 3. The preparation method of the present application, under the action of the alternating electric field, the orientation degree of the particles in the filler is higher, and more heat-conducting chains, i.e., heat-conducting paths, are formed inside the silicone potting compound. The prepared silicone potting compound has good thermal conductivity, flame retardancy and good viscosity, and is suitable for the field of electronic industry. The cross-linking density generated by the combined action of the vinyl-terminated silicone oil, hydrogen-containing silicone oil, filler, inhibitor, and Custer catalyst is moderate, and the mechanical properties are good. DETAILED DESCRIPTION
[0042] The present application is described in further detail below.
[0043] Introduction of raw materials The following is an introduction to raw materials.
[0044] Table 1 Introduction of raw materials
[0045]
[0046]
[0047] Preparation Example
[0048] Preparation Example 1
[0049] Preparation Example 1
[0050] The preparation method of modified alumina particles is as follows:
[0051] S1. Mix 68 parts of aluminum oxide micron particles, 56 parts of a precipitant, and 1100 parts of distilled water to obtain a reaction mixture; the particle size of the aluminum oxide micron particles is 16 microns,
[0052] S2. The reaction mixture was stirred and dispersed at a speed of 3000 r / min, alum was added while stirring, and after stirring for 7 minutes, stirring was stopped, and a precipitation reaction was carried out, which was maintained at 35° C. for 1 hour, and then filtered to collect the aluminum oxide precipitate with aluminum hydroxide deposited on the surface;
[0053] S3. The collected alumina precipitate was dried in an oven at 120°C for 2h, then treated in a high temperature sintering furnace at 800°C for 2.5h, and then treated in a high temperature sintering furnace at 1450°C for 1h, taken out, and dried at room temperature for 48h to obtain nano-alumina-coated alumina micron particles;
[0054] S4. Add silane coupling agent KH-792 to the nano-alumina-coated alumina micron particles, mix them evenly at a temperature of 35° C. to obtain modified alumina particles, the core particle size of the modified alumina particles is 16 microns, and the shell thickness of the modified alumina particles is 160 nm.
[0055] Preparation Example 2
[0056] The preparation method of modified alumina particles is as follows:
[0057] S1. 84 parts of aluminum oxide micron particles, 42 parts of a precipitant, and 1350 parts of distilled water were mixed to obtain a reaction mixture; the particle size of the aluminum oxide micron particles was 16 microns,
[0058] S2. The reaction mixture was stirred and dispersed at a speed of 2200 r / min, alum was added while stirring, and after stirring for 9 minutes, stirring was stopped, and a precipitation reaction was carried out, which was maintained at 30° C. for 1.5 hours, and then filtered to collect the aluminum oxide precipitate with aluminum hydroxide deposited on the surface;
[0059] S3. The collected alumina precipitate was dried in an oven at 100 ° C for 4 h, then treated in a high-temperature sintering furnace at 680 ° C for 3.5 h, and then treated in a high-temperature sintering furnace at 1300 ° C for 2.5 h, taken out, and dried at room temperature for 24 h to obtain nano-alumina-coated alumina micron particles;
[0060] S4. Add silane coupling agent KH-792 to the nano-alumina-coated alumina micron particles, mix them evenly at a temperature of 55° C. to obtain modified alumina particles, the core particle size of the modified alumina particles is 20 microns, and the shell thickness of the modified alumina particles is 120 nm.
[0061] Preparation Example 3
[0062] The preparation method of modified alumina particles is as follows:
[0063] S1. 76 parts of aluminum oxide micron particles, 49 parts of precipitant, and 1175 parts of distilled water were mixed to obtain a reaction mixture; the particle size of the aluminum oxide micron particles was 18 microns,
[0064] S2. The reaction mixture was stirred and dispersed at a speed of 1600 r / min, alum was added while stirring, and after stirring for 8 minutes, stirring was stopped, and a precipitation reaction was carried out, and the temperature was kept at 32.5° C. for 1.25 hours, and then filtered to collect the aluminum oxide precipitate with aluminum hydroxide deposited on the surface;
[0065] S3. The collected alumina precipitate was dried in an oven at 110°C for 3h, then treated in a high temperature sintering furnace at 740°C for 3h, and then treated in a high temperature sintering furnace at 1375°C for 1.75h, taken out, and dried at room temperature for 36h to obtain nano-alumina-coated alumina micron particles;
[0066] S4. Add silane coupling agent KH-792 to the nano-alumina-coated alumina micron particles, mix them evenly at a temperature of 45° C. to obtain modified alumina particles, the core particle size of the modified alumina particles is 18 microns, and the shell thickness of the modified alumina particles is 140 nm.
[0067] Preparation Example 4
[0068] The preparation method of the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is as follows:
[0069] Prepare chitosan acetic acid aqueous solution: dissolve 0.5 parts of chitosan in 1.5wt% acetic acid solution;
[0070] The first core-shell reaction: 8 parts of polybutylene adipate terephthalate were uniformly dispersed in 230 parts of deionized water, and the prepared chitosan acetic acid aqueous solution was added dropwise. After stirring for 3 minutes, the mixture was centrifuged for 5 minutes at a centrifugal speed of 3000 r / min to obtain a precipitate, which was then washed with deionized water to obtain a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan as the shell.
[0071] Prepare Si(C00H)2 ammonia solution: dissolve 0.4 parts of Si(C00H)2 in 9.5wt% dilute ammonia water, adjust the pH to 8, and prepare Si(C00H)2 ammonia solution;
[0072] The second core-shell reaction: a core-shell structure complex with polybutylene adipate terephthalate as the core and chitosan as the shell is uniformly dispersed in 300 parts of deionized water to prepare a suspension, and Si(C00H)2 ammonia solution is added to the suspension, stirred for 3 minutes, and centrifuged to obtain a precipitate, which is washed twice with deionized water, ball-milled for 60 minutes, and vacuum-dried at 65°C for 18 hours. The precipitate is sieved to obtain a core-shell structure complex with a particle size of 15 microns, with polybutylene adipate terephthalate as the core and chitosan and Si as the shell.
[0073] Preparation Example 5
[0074] The preparation method of the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is as follows:
[0075] Prepare chitosan acetic acid aqueous solution: dissolve 1.5 parts of chitosan in 0.5wt% acetic acid solution;
[0076] The first core-shell reaction: 12 parts of polybutylene adipate terephthalate were uniformly dispersed in 180 parts of deionized water, and the prepared chitosan acetic acid aqueous solution was added dropwise. After stirring for 5 minutes, the mixture was centrifuged for 3 minutes at a centrifugal speed of 4000 r / min to obtain a precipitate, which was then washed with deionized water to obtain a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan as the shell.
[0077] Prepare Si(C00H)2 ammonia solution: dissolve 0.2 parts of Si(C00H)2 in 10.5wt% dilute ammonia water, adjust the pH to 8, and prepare Si(C00H)2 ammonia solution;
[0078] The second core-shell reaction: a core-shell structure complex with polybutylene adipate terephthalate as the core and chitosan as the shell is uniformly dispersed in 200 parts of deionized water to prepare a suspension, and Si(C00H)2 ammonia solution is added to the suspension, stirred for 5 minutes, and centrifuged to obtain a precipitate, which is washed twice with deionized water, ball-milled for 30 minutes, and vacuum-dried at 85°C for 12 hours. The precipitate is sieved to obtain a core-shell structure complex with a particle size of 10 microns, with polybutylene adipate terephthalate as the core and chitosan and Si as the shell.
[0079] Preparation Example 6
[0080] The preparation method of the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is as follows:
[0081] Prepare chitosan acetic acid aqueous solution: dissolve 1.0 part of chitosan in 1.0wt% acetic acid solution;
[0082] The first core-shell reaction: 10 parts of polybutylene adipate terephthalate were uniformly dispersed in 205 parts of deionized water, and the prepared chitosan acetic acid aqueous solution was added dropwise. After stirring for 4 minutes, the mixture was centrifuged for 4 minutes at a centrifugal speed of 3500 r / min to obtain a precipitate, which was then washed with deionized water to obtain a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan as the shell.
[0083] Prepare Si(C00H)2 ammonia solution: dissolve 0.3 parts of Si(C00H)2 in 10wt% dilute ammonia water, adjust the pH to 8, and prepare Si(C00H)2 ammonia solution;
[0084] The second core-shell reaction: a core-shell structure complex with polybutylene adipate terephthalate as the core and chitosan as the shell is uniformly dispersed in 250 parts of deionized water to obtain a suspension, and Si(C00H)2 ammonia solution was added to the suspension, stirred for 4 minutes, and centrifuged to obtain a precipitate, which was washed twice with deionized water, ball-milled for 45 minutes, and vacuum-dried at 75°C for 15 hours. The core-shell structure complex with a particle size of 12 microns and polybutylene adipate terephthalate as the core and chitosan and Si as the shell was obtained.
[0085] Example
[0086] Example 1
[0087] A silicone potting adhesive comprises the following components by weight: 90 parts of vinyl-terminated silicone oil, 15 parts of hydrogen-containing silicone oil, 360 parts of filler, 0.6 parts of inhibitor, and 0.05 parts of Custer catalyst; the vinyl-terminated silicone oil is a combination of vinyl-terminated silicone oil with a viscosity of 400 mPa·s and vinyl-terminated silicone oil with a viscosity of 800 mPa·s, and the ratio of the vinyl-terminated silicone oil with a viscosity of 400 mPa·s and the vinyl-terminated silicone oil with a viscosity of 800 mPa·s is 1:2; the filler is a combination of modified alumina particles and cerium dioxide nanoparticles, and the filler also includes polybutylene adipate terephthalate as The core-shell structure composite with chitosan and Si as the shell; the ratio of modified alumina particles, cerium dioxide nanoparticles, and a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 1:0.2:8; the modified alumina particles are prepared by the modified alumina particles prepared in Preparation 1, the particle size of the cerium dioxide nanoparticles is 50 nanometers, the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is prepared by Preparation Example 5. The inhibitor is alkynyl cyclohexanol, and the Custer catalyst is chloroplatinic acid-divinyltetramethyldisiloxane complex.
[0088] The preparation method of the above-mentioned silicone potting adhesive comprises the following steps:
[0089] Under vacuum conditions, the vinyl-terminated silicone oil and filler are stirred evenly at 80°C in a high-speed disperser to obtain a base material, which is then allowed to cool until the temperature of the base material drops to 50°C. Appropriate amounts of hydrogenated silicone oil, inhibitor, and Custer catalyst are added and mixed evenly. Finally, the mixture is placed in a vacuum drying oven for vacuum degassing for 15 minutes, poured into a mold, and cured in a 50Hz AC electric field with an intensity of 10 kV·mm-1 and a temperature of 130°C for 2.5 hours to obtain a silicone potting adhesive.
[0090] Example 2
[0091] A silicone potting adhesive comprises the following components by weight: 120 parts of vinyl-terminated silicone oil, 8 parts of hydrogen-containing silicone oil, 580 parts of filler, 0.1 parts of inhibitor, and 0.20 parts of Custer catalyst; the vinyl-terminated silicone oil is a combination of vinyl-terminated silicone oil with a viscosity of 400 mPa·s and vinyl-terminated silicone oil with a viscosity of 800 mPa·s, and the ratio of the vinyl-terminated silicone oil with a viscosity of 400 mPa·s and the vinyl-terminated silicone oil with a viscosity of 800 mPa·s is 1:3; the filler is a combination of modified alumina particles and cerium dioxide nanoparticles, and the filler also includes polybutylene adipate terephthalate as The core-shell structure composite with chitosan and Si as the shell; the ratio of modified alumina particles, cerium dioxide nanoparticles, and a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 1:0.9:1; the modified alumina particles are prepared by the modified alumina particles prepared in Preparation 2, the particle size of the cerium dioxide nanoparticles is 50 nanometers, the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is prepared by Preparation Example 4. The inhibitor is alkynyl cyclohexanol, and the Custer catalyst is chloroplatinic acid-divinyltetramethyldisiloxane complex.
[0092] The preparation method of the above-mentioned silicone potting adhesive comprises the following steps:
[0093] Under vacuum conditions, the vinyl-terminated silicone oil and filler are stirred evenly at 110°C in a high-speed disperser to obtain a base material, which is then allowed to cool until the base material temperature drops to 40°C. Appropriate amounts of hydrogenated silicone oil, inhibitor, and Custer catalyst are added and mixed evenly. Finally, the mixture is placed in a vacuum drying oven for vacuum degassing for 25 minutes, poured into a mold, and cured at 170°C for 1.5 hours in a 50Hz AC electric field with an intensity of 9 kV·mm-1 to obtain a silicone potting adhesive.
[0094] Example 3
[0095] A silicone potting adhesive comprises the following components by weight: 105 parts of vinyl-terminated silicone oil, 11.5 parts of hydrogen-containing silicone oil, 470 parts of filler, 0.035 parts of inhibitor, and 0.125 parts of Custer catalyst; the vinyl-terminated silicone oil is a combination of vinyl-terminated silicone oil with a viscosity of 400 mPa·s and vinyl-terminated silicone oil with a viscosity of 800 mPa·s, and the ratio of the vinyl-terminated silicone oil with a viscosity of 400 mPa·s and the vinyl-terminated silicone oil with a viscosity of 800 mPa·s is 1:2.5; the filler is a combination of modified alumina particles and cerium dioxide nanoparticles; the filler also comprises a core-shell structure with polybutylene adipate terephthalate as the core and chitosan and Si as the shell. The invention discloses a composite material comprising modified alumina particles, cerium dioxide nanoparticles, and a core-shell structure composite material having polybutylene adipate terephthalate as the core and chitosan and Si as the shell in a ratio of 1:0.5:4.5; the modified alumina particles are prepared using the modified alumina particles prepared in Preparation 3, the particle size of the cerium dioxide nanoparticles is 50 nm, the core-shell structure composite material having polybutylene adipate terephthalate as the core and chitosan and Si as the shell is prepared using the core-shell structure composite material having polybutylene adipate terephthalate as the core and chitosan and Si as the shell prepared in Preparation Example 6, the inhibitor is alkynyl cyclohexanol, and the Castor catalyst is chloroplatinic acid-divinyltetramethyldisiloxane complex.
[0096] The preparation method of the above-mentioned silicone potting adhesive comprises the following steps:
[0097] Under vacuum conditions, vinyl-terminated silicone oil and filler are stirred evenly at 95°C in a high-speed disperser to obtain a base material, which is then cooled and cooled to 45°C. An appropriate amount of hydrogenated silicone oil, inhibitor, and Custer catalyst are added and mixed evenly. Finally, the mixture is placed in a vacuum drying oven for vacuum degassing for 20 minutes and poured into a mold at a strength of 9.5 kV·mm -1 The silicone potting adhesive was obtained by curing the mixture in a 50 Hz AC electric field and at a temperature of 150°C for 2 hours.
[0098] Comparative Example
[0099] Comparative Example 1
[0100] The difference between Comparative Example 1 and Example 3 is that aluminum hydroxide particles with a particle size of 18 microns are used instead of modified aluminum oxide particles.
[0101] Comparative Example 2
[0102] The difference between Comparative Example 2 and Example 3 is that aluminum hydroxide particles with a particle size of 50 nanometers are used instead of cerium dioxide nanoparticles.
[0103] Comparative Example 3
[0104] The difference between Comparative Example 3 and Example 3 is that aluminum hydroxide particles with a particle size of 12 μm are used instead of the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell.
[0105] Comparative Example 4
[0106] The difference between Comparative Example 4 and Example 3 is that all fillers are aluminum hydroxide particles with a particle size of 12 microns.
[0107] Comparative Example 5
[0108] Commercially available thermally conductive flame retardant silicone potting compound.
[0109] Performance Testing
[0110] The performance of the silicone potting adhesives of Examples 1-3 and Comparative Examples 1-5 was tested.
[0111] The detection method is as follows:
[0112] 1. Viscosity: measured in accordance with GB / T 10247-2008.
[0113] 2. Hardness: Shore A hardness tested according to GB / T 531-2008;
[0114] 3. Mechanical properties
[0115] The tensile strength and elongation at break were measured using an electronic universal testing machine in accordance with GB / T 528-2009. The specimen was dumbbell-shaped, 2 mm thick, and the tensile rate was 500 mm / min.
[0116] 4. Electrical properties
[0117] (1) Dielectric strength: Tested according to GB / T1408.1-2006.
[0118] (2) Volume resistivity: Tested according to GB / T1410-2006.
[0119] 5. Thermal conductivity
[0120] Thermal conductivity: tested according to GB / T 10297-2015 standard.
[0121] 6. Flame retardant properties
[0122] Vertical burning grade: measured according to UL94-2009 standard using a horizontal vertical burning test machine.
[0123] The test results are as follows:
[0124] Table 2 Test results
[0125]
[0126]
[0127] It can be seen from the data in the above table that the thermal conductivity of the silicone potting glue of Examples 1-3 is all above 3.0W / m·K, indicating that the thermal conductivity of Examples 1-3 is good. The flame retardant grade of Example 1-3 is V-0, indicating that the flame retardancy of Example 1-3 is good. In addition, the viscosity of Examples 1-3 is all above 9500mPa·s, indicating that the viscosity of Example 1-3 is good. Moreover, the mechanical properties such as hardness, tensile strength, and elongation at break of Examples 1-3 all meet the requirements. In addition, the electrical properties such as dielectric strength and volume resistivity of Examples 1-3 also meet the requirements. It shows that the silicone potting glue of the present application has good thermal conductivity, flame retardancy and viscosity on the basis of the mechanical properties and electrical properties meeting the requirements.
[0128] Comparing Example 3 with Comparative Example 1, it is shown that aluminum hydroxide particles cannot replace modified aluminum oxide particles, which means that modified aluminum oxide particles play an important role in various properties of the silicone potting compound of the present application, especially thermal conductivity, flame retardancy and viscosity, and also have a certain influence on mechanical properties.
[0129] Comparing Example 3 with Comparative Example 2, it is shown that aluminum hydroxide particles cannot replace cerium dioxide nanoparticles, indicating that cerium dioxide nanoparticles play an important role in the various properties of the silicone potting compound of the present application, especially thermal conductivity, flame retardancy and viscosity, and also have a certain influence on the mechanical properties.
[0130] Comparing Example 3 with Comparative Example 2, it is shown that aluminum hydroxide particles cannot replace cerium dioxide nanoparticles, indicating that cerium dioxide nanoparticles play an important role in the various properties of the silicone potting compound of the present application, especially thermal conductivity, flame retardancy and viscosity, and also have a certain influence on the mechanical properties.
[0131] Comparing Example 3 with Comparative Example 3, it is shown that aluminum hydroxide particles cannot replace the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell, which shows that the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell plays an important role in the various properties of the silicone potting adhesive of the present application, especially thermal conductivity, flame retardancy and viscosity, and also has a certain influence on the mechanical properties.
[0132] Comparison of Example 3 with Comparative Example 4 shows that aluminum hydroxide particles cannot replace modified alumina particles, cerium dioxide nanoparticles, and a core-shell structure composite having polybutylene adipate terephthalate as a core and chitosan and Si as a shell.
[0133] In summary, it is shown that modified alumina particles, cerium dioxide nanoparticles, and polybutylene adipate terephthalate have a synergistic effect, which plays an important role in the various properties of the silicone potting adhesive of the present application, especially thermal conductivity, flame retardancy and viscosity, and also has a certain influence on the mechanical properties.
[0134] Comparison of Example 3 and Comparative Example 5 shows that the thermal conductivity, flame retardancy and viscosity of the silicone potting adhesive of the present application are significantly better than those of the commercially available thermally conductive and flame retardant silicone potting adhesive.
[0135] Therefore, the above specific embodiments are merely explanations of the present application, and they are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the present application without any creative contribution as needed, but they should all be included in the scope of protection of the present application.
Claims
1. A silicone potting compound, characterized in that: The invention comprises the following components by weight: 90-120 parts of vinyl-terminated silicone oil, 8-15 parts of hydrogen-containing silicone oil, 360-580 parts of filler, 0.1-0.6 parts of inhibitor, and 0.05-0.20 parts of Custer catalyst; the filler is a combination of modified alumina particles and cerium dioxide nanoparticles, and the filler also comprises a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell; the ratio of the modified alumina particles, cerium dioxide nanoparticles, and the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 1:(0.2-0.9):(1-8); The preparation method of the modified alumina particles is as follows: S1. Mix 68-84 parts of aluminum oxide micron particles, 42-56 parts of a precipitant, and 1100-1350 parts of distilled water to obtain a reaction mixture; S2. The reaction mixture is stirred and dispersed at a speed of 2200-3000 r / min, alum is added while stirring, and after stirring for 7-9 minutes, stirring is stopped, and a precipitation reaction is carried out, and the temperature is maintained at 30-35° C. for 1-1.5 hours, and then filtered to collect the aluminum oxide precipitate with aluminum hydroxide deposited on the surface; S3. The collected alumina precipitate was dried in an oven at 100-120°C for 2-4h, then treated in a high temperature sintering furnace at 680-800°C for 2.5-3.5h, and then treated in a high temperature sintering furnace at 1300-1450°C for 1-2.5h, taken out, and dried at room temperature for 24-48h to obtain nano-alumina-coated alumina micron particles; S4. Adding a silane coupling agent to the nano-alumina-coated alumina micron particles, mixing at a temperature of 35-55° C. to obtain modified alumina particles; The core particle size of the modified alumina particles is 16-20 microns, and the shell thickness of the modified alumina particles is 120-160 nm; The particle size of the cerium dioxide nanoparticles is 50 nm; The preparation method of the core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is as follows: Prepare chitosan acetic acid aqueous solution: dissolve 0.5-1.5 parts of chitosan in 0.5-1.5wt% acetic acid solution; The first core-shell reaction: 8-12 parts of polybutylene adipate terephthalate are uniformly dispersed in 180-230 parts of deionized water, and the prepared chitosan acetic acid aqueous solution is added dropwise, and after stirring for 3-5 minutes, centrifugation is performed for 3-5 minutes at a centrifugal speed of 3000-4000r / min to obtain a precipitate, and then washed with deionized water to obtain a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan as the shell; Prepare Si(COOH)2 ammonia solution: dissolve 0.2-0.4 parts of Si(COOH)2 in 9.5-10.5wt% dilute ammonia water, adjust the pH to 8, and prepare Si(COOH)2 ammonia solution; wherein the model of Si(COOH)2 is BY16-750; Second core-shell reaction: a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan as the shell is uniformly dispersed in 200-300 parts of deionized water to prepare a suspension, Si(COOH)2 ammonia solution is added to the suspension, stirred for 3-5 minutes, centrifuged to obtain a precipitate, washed twice with deionized water, ball milled for 30-60 minutes, vacuum dried at 65-85°C for 12-18 hours, sieved to obtain a core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell; The core-shell structure composite with polybutylene adipate terephthalate as the core and chitosan and Si as the shell is 10-15 microns.
2. The organic silicone potting adhesive according to claim 1, characterized in that: The precipitant is aluminum sulfate.
3. The organic silicone potting adhesive according to claim 1, characterized in that: The vinyl-terminated silicone oil is a combination of vinyl-terminated silicone oil with a viscosity of 400mPa·s and vinyl-terminated silicone oil with a viscosity of 800mPa·s, and the ratio of the vinyl-terminated silicone oil with a viscosity of 400mPa·s and the vinyl-terminated silicone oil with a viscosity of 800mPa·s is 1:(2-3).
4. The organic silicone potting adhesive according to claim 1, characterized in that: The inhibitor is alkynyl cyclohexanol.
5. A method for preparing a silicone potting compound according to any one of claims 1 to 4, characterized in that: The following steps are included: Under vacuum conditions, the vinyl-terminated silicone oil and filler are stirred evenly at a temperature of 80-110°C to obtain a base material, which is then cooled to a temperature of 40-50°C. An appropriate amount of hydrogenated silicone oil, inhibitor, and Custer catalyst are added and mixed evenly. Finally, the mixture is vacuum degassed for 15-25 minutes and poured into a mold at a strength of 9-10 kV·mm -1 The organic silicone potting adhesive is cured for 1.5-2.5 hours under a 50Hz alternating current electric field and a temperature of 130-170°C to obtain the organic silicone potting adhesive.
Citation Information
Patent Citations
Novel organosilicone pouring sealant
CN105838322A
Coated modified aluminum oxide and preparation method thereof, and epoxy composite insulating material
CN110669257A